Paracrine signaling in the prostatic stroma: A novel role for the telocytes revealed in rdents’ ventral prostate - Sanches, Bruno D. A. [UNESP]; Corradi, Lara S. [UNESP]; Vilamaior, Patricia S. L. [UNESP]; Taboga, Sebastiï¿½o R. [UNESP] (Springer Nature, 2016)
The telocytes have recently been described in the prostate gland. In mature gland, they exist in close association with the acini and their telopodes form networks whose functions remain unclear. In this chapter, our group gives a brief introduction to telocytes and explores the history that led to such a concept and then discusses hypotheses and presents new evidences about the roles exerted by telocytes in the prostate. First is given emphasis on the role that these cells possibly play in paracrine signaling employed in the differentiation of smooth muscle periacinar are then discussed other roles potentially performed by telocytes in the prostate, such as the organizational, where these cells would act in order to delimit stromalmicroenvironments, thereby assisting the differentiation of the prostatic anatomical components. In addition, the pacemaker function of smooth muscle cells contraction, as evidenced by the presence of caveolae and gap-type junction and, finally, the role of telocytes in prostate remodeling and the possible action as adult progenitor cells. Generally speaking, the chapter reaffirms the existence of telocytes as distinct cells of other stromal cells and the importance of this new cell type for normal metabolism and prostate development.